2023
DOI: 10.3390/toxins15050342
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Antibody Formation with OnabotulinumtoxinA (BOTOX®) Treatment from Global Registration Studies across Multiple Indications: A Meta-Analysis

Abstract: Though the formation of neutralizing antibodies (NAbs) during treatment with botulinum neurotoxin is rare, their presence may nonetheless affect the biological activity of botulinum toxin and negatively impact clinical response. The goal of this updated meta-analysis was to evaluate and characterize the rate of NAb formation using an expanded dataset composed of 33 prospective placebo-controlled and open-label clinical trials with nearly 30,000 longitudinal subject records prior to and following onabotulinumto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
1
9
0
1
Order By: Relevance
“…This study also showed that neutralizing antibody status can vary over time, as only 4/2240 had a positive test at the final post-treatment study visit. A change in antibody status over time has also been reported by others [213,215,226] and, notably, in a recent meta-analysis of 5876 subjects treated with onabotA across 10 therapeutic and aesthetic indications in which 0.5% developed neutralizing antibodies at some point but only 0.3% remained positive at the end of the study [213].…”
Section: Secondary Non-response: Usually Not Due To Neutralizing Anti...supporting
confidence: 74%
“…This study also showed that neutralizing antibody status can vary over time, as only 4/2240 had a positive test at the final post-treatment study visit. A change in antibody status over time has also been reported by others [213,215,226] and, notably, in a recent meta-analysis of 5876 subjects treated with onabotA across 10 therapeutic and aesthetic indications in which 0.5% developed neutralizing antibodies at some point but only 0.3% remained positive at the end of the study [213].…”
Section: Secondary Non-response: Usually Not Due To Neutralizing Anti...supporting
confidence: 74%
“… 31 , 33 The panelists agreed that performing a full repeat treatment in less than 3 months should be avoided due to the risk of neutralizing antibodies; 34 however, a recent meta-analysis by Jankovic et al found no clear relationship between neutralizing antibody formation and dosing interval, with the overall incidence of neutralizing antibodies being low (≤1.4%). 35 …”
Section: Resultsmentioning
confidence: 99%
“…31,33 The panelists agreed that performing a full repeat treatment in less than 3 months should be avoided due to the risk of neutralizing antibodies; 34 however, a recent meta-analysis by Jankovic et al found no clear relationship between neutralizing antibody formation and dosing interval, with the overall incidence of neutralizing antibodies being low (≤1.4%). 35 To ensure optimal results, some panelists have found it useful to request that patients bring videos to their next appointment demonstrating their facial muscle movements 14 days posttreatment. This technique tends to be popular with patients in clinical practice.…”
Section: Follow-upmentioning
confidence: 99%
“…It is important to note that the study by Hefter et al merged data on OnabotulinumtoxinA and AbobotulinumtoxinA into a single group, despite these being distinct formulations with differing potencies. Jankovic et al’s meta-analysis, spanning 33 clinical trials with nearly 30,000 subject records, found an overall low NAb formation rate of 0.5% following OnabotulinumtoxinA treatment [ 155 ]. Importantly, this study showed no clear association between NAb-positive events and higher doses, number of treatment cycles, or other clinical variables.…”
Section: Discussionmentioning
confidence: 99%